Intrahepatic hemodynamics in children with dynamic and inflammatory cholepathias - L. A. Semenyuk; N. K. Bychkova (Бюллетень сибирской медицины)
Ultrasound dopplerography can reveal minimal disfunctions of intrahepatic hemodynamics. Linear speed of hepatic artery and hepatic vein (peak S and D) rises in the presence of dynamic and to a greater extent organic (inflammatory) cholepathias. The increase of blood flow speed occurs when vessel radius expands. This phenomenon can be explained by dilation of intrahepatic vessels which is more defined when the matter concerns inflammatory cholepathias and less defined among dynamic ones. Indices of intrahepatic hemodynamics may serve as indirect signs of given diseases among children and may reveal pathology on the earliest stages of its development.